Binder for lithium ion battery and preparation method of binder
By using special adhesives in lithium -ion batteries, including inorganic nanoparticles, acrylic ethyl, polyethylene, polyurethane, tetraonal polyacrylates, and modified carboxymethyl cellulose, the volume of silicon particles is solved The problem of capacity attenuation caused by expansion has achieved better bonding and electrochemical properties.
Patent Information
- Application Number
- CN202411919998.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-01-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The volume expansion of silicon particles in lithium-ion batteries leads to the crushing of the electrode material structure and rapid attenuation of capacity, limiting the practical application of silicon-based anode in lithium batteries.
A bonding agent includes a nuclear core, the first cover layer, and the second cover layer. The nuclear core is inorganic nanoparticles. The second cover layer is composed of four -arm polyacrylic acid cluster, modified carboxymethyl cellulose and emulsifier. Through specific component proportions and structural design, it significantly suppress the volume expansion of silicon and achieve the adhesion and repair of silicon particles Essence
Effectively reduce the rapid decay of lithium battery capacity caused by the volume expansion of silicon particles, and improves the adhesion and electrochemical performance of the negative silicon negative pole.
Smart Images

Figure CN119351001A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a binder for lithium ion batteries, in particular to a binder for silicon negative electrodes of lithium ion batteries and a preparation method thereof. Background Art
[0002] Lithium-ion batteries are widely used in portable electronic devices and electric vehicles, and with the continuous development of lithium-ion battery technology, electronic products have been lightweight and miniaturized. In traditional lithium-ion batteries, graphite is generally used as the negative electrode material. Since the theoretical capacity of graphite is low (372 mA·h / g), it cannot meet the demand for high energy density, so the application of graphite negative electrode in electric vehicles is also hindered. However, silicon (Si) can solve this problem by replacing graphite as the negative electrode material. Because of its high theoretical capacity (4200 mA·h / g), it is very promising to become the negative electrode material of the next generation of lithium-ion batteries.
[0003] However, during the cycle process, the volume of silicon particles will expand (>300%), causing the structure of the electrode material to break up and the capacity to decay rapidly, thus limiting the practical application of silicon-based negative electrodes in lithium batteries. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a binder for lithium batteries that can effectively reduce the rapid attenuation of lithium battery capacity caused by the volume expansion of silicon particles. At the same time, the present invention also provides a preparation method of the binder and its application in lithium batteries.
[0005] To achieve the above object, on the one hand, the present invention provides a binder for lithium ion batteries, the binder comprising a core, a first coating layer and a second coating layer sequentially coated on the outer surface of the core; The core is an inorganic nanoparticle; the first coating layer includes ethyl acrylate, polyvinyl alcohol, polyurethane and a first emulsifier; The second coating layer includes four-arm polyacrylic acid copolymer, modified carboxymethyl cellulose and a second emulsifier, and the mass ratio of the four-arm polyacrylic acid copolymer to the modified carboxymethyl cellulose is (1-3): (5-8).
[0006] The binder for lithium-ion batteries of the present invention comprises a core and a first coating layer and a second coating layer sequentially coated on the outer surface of the core, wherein the core is made of inorganic nanoparticles, and the first coating layer is made of ethyl acrylate, polyvinyl alcohol, polyurethane and a first emulsifier, and the second coating layer is made of four-arm polyacrylic acid copolymer, modified carboxymethyl cellulose and a second emulsifier. In the binder, the core is made of inorganic nanoparticles, which give the binder core a certain rigidity; the first coating layer has suitable elasticity through the screening and preparation of the raw materials; and a specific ratio of four-arm polyacrylic acid copolymer and modified carboxymethyl cellulose is selected in the second coating layer, and the combination of the two can not only achieve the bonding performance requirements for the silicon negative electrode, but also significantly inhibit the volume expansion of silicon. The binder is designed with an overall structure of a core, a first coating layer and a second coating layer. The second coating layer has a strong bonding effect on the silicon negative electrode, and the core, the first coating layer and the second coating layer cooperate to effectively inhibit the volume expansion of silicon, and can repair and rebuild the fracture surface of the material after mechanical damage occurs due to volume expansion of silicon particles, so that the silicon particles maintain a relatively fixed position, realize elastic expansion of silicon particles, and effectively reduce the problem of rapid capacity decay of lithium batteries caused by volume expansion of silicon particles.
[0007] The four-arm polyacrylic acid copolymer is a polyacrylic acid homopolymer (4A-PAA) with a four-arm molecular structure prepared by combining ATRP polymerization technology with ester hydrolysis. The synthesis method thereof can be found in LUO C, WU XF, ZHANG T, et al. A Four-Armed Polyacrylic Acid Homopolymer Binder with Enhanced Performance for SiOx / Graphite Anode[J]. Macromolecular Materials and Engineering, 2021, 306(1): 2000525.
[0008] Preferably, the modified carboxymethyl cellulose in the second coating layer is citric acid modified carboxymethyl cellulose. The citric acid modified carboxymethyl cellulose can be purchased from the market or made at home. The preparation method of the citric acid modified carboxymethyl fiber includes but is not limited to the following steps: (1) adding citric acid powder to a solvent and stirring in a water bath to dissolve the powder to obtain a citric acid solution; (2) Ultrapure water and carboxymethyl cellulose are added to a citric acid solution, and the mixture is stirred in a water bath to react, thereby obtaining citric acid-modified carboxymethyl cellulose.
[0009] Preferably, in the second coating layer, the sum of the mass percentages of the four-arm polyacrylic acid copolymer and the modified carboxymethyl cellulose is 50-80%. In the second coating layer, the sum of the mass percentages of the four-arm polyacrylic acid copolymer and the modified carboxymethyl cellulose is 50-80%. If the sum of the two contents is too little, it not only affects the bonding performance of the silicon negative electrode, but also significantly affects the inhibitory effect on the volume expansion of the silicon negative electrode. If the content of the two is too high, it affects the dispersion uniformity of the two in the second coating layer, and also has an adverse effect on its bonding performance and the inhibitory effect on the volume expansion of the silicon negative electrode. The sum of the mass percentages of the four-arm polyacrylic acid copolymer and the modified carboxymethyl cellulose can be, for example, 50%, 52%, 54%, 56%, 58%, 60%, 62%, 64%, 66%, 68%, 70%, 72%, 74%, 76%, 78%, 80%, etc. and the range formed by any two point values. More preferably, in the second coating layer, the sum of the mass percentages of the four-arm polyacrylic acid copolymer and the modified carboxymethyl cellulose is 60-80%.
[0010] More preferably, the mass ratio of the four-arm polyacrylic acid copolymer to the modified carboxymethyl cellulose is 2: (5~8). The four-arm polyacrylic acid copolymer and the modified carboxymethyl cellulose have a common assisting effect. The four-arm polyacrylic acid copolymer is a multi-arm molecular structure, which can reduce the molecular regularity and intramolecular hydrogen bond interaction of polyacrylic acid, and can enhance the toughness and adhesion of the binder. The modified carboxymethyl cellulose has a specific network structure, which can not only enhance the adhesion of the binder, but also enable the binder to have a certain fixing effect on the silicon particles, keeping the silicon particles in a relatively fixed position, thereby achieving the elastic expansion of the silicon particles. The inventors of the present application found in the experiment that when the two are combined, the amount ratio of the two has a direct impact on the adhesion of the binder and the effect of inhibiting the volume expansion of the silicon negative electrode. If the ratio of the two is too large or too small, it cannot have both strong adhesion and the effect of inhibiting the volume expansion of the silicon negative electrode. When the two are in a suitable ratio range, high adhesion and the effect of inhibiting the volume expansion of silicon particles can be achieved.
[0011] Preferably, the inorganic nanoparticles are at least one of sodium tripolyphosphate powder, silicon dioxide nanoparticles, and titanium dioxide nanoparticles; the particle size of the sodium tripolyphosphate powder is 1 to 1000 nm. More preferably, the particle size of the sodium tripolyphosphate powder is 100 to 600 nm.
[0012] Preferably, the first emulsifier and the second emulsifier are each independently selected from at least one of octylphenol polyoxyethylene ether, polyoxyethylene-8-octylphenyl ether, and oleic acid polyoxyethylene ether. More preferably, the first emulsifier and the second emulsifier are a mixture of octylphenol polyoxyethylene ether and oleic acid polyoxyethylene ether, and the mass ratio of the two is preferably but not limited to (1-4):1.
[0013] Preferably, the sum of the mass percentages of ethyl acrylate, polyvinyl alcohol and polyurethane in the first coating layer is 65-85%. If the total content of ethyl acrylate, polyvinyl alcohol and polyurethane in the first coating layer is too low, the elasticity and other properties of the first coating layer will be affected, thereby directly affecting the inhibition of the volume expansion of the silicon negative electrode. More preferably, the sum of the mass percentages of ethyl acrylate, polyvinyl alcohol and polyurethane in the first coating layer is 70-80%.
[0014] Preferably, the mass ratio of ethyl acrylate, polyvinyl alcohol and polyurethane in the first coating layer is 5: (2-3): 1. The inventors of the present application have found that the mass ratio of ethyl acrylate, polyvinyl alcohol and polyurethane in the first coating layer needs to be appropriate so that the first coating layer can be closely attached to the core and the second coating layer, and can have appropriate elasticity and other properties, so as to achieve a synergistic inhibition effect on the volume expansion of the silicon negative electrode.
[0015] Preferably, the mass ratio of the core to the first coating layer and the second coating layer is: core: (first coating layer + second coating layer) = (1-3): (2-5).
[0016] Preferably, the mass ratio of the first coating layer to the second coating layer is (1-2):1.
[0017] The ratio of the amount of the core, the first coating layer, and the second coating layer has a direct impact on the bonding performance of the binder and the inhibition and repair effect on the volume expansion of the silicon negative electrode. After screening and determining the raw materials of the first coating layer and the second coating layer, the inventors of the present application further found through repeated experiments that when the core and the two coating layers meet the core: the mass sum of the two coating layers is (1~3): (2~5), and more preferably 2: (3~5), the core and the two coating layers cooperate with each other, and the volume expansion inhibition effect of the silicon negative electrode material is more significant. The mass ratio of the first coating layer and the second coating layer also has a direct impact on the bonding force of the binder and the inhibition of the volume expansion of the silicon negative electrode. The mass ratio of the first coating layer and the second coating layer is preferably (1~2): 1. The combination of the two can achieve excellent comprehensive performance of the binder.
[0018] On the other hand, the present invention also provides a method for preparing the binder as described above. To achieve this purpose, the technical solution adopted by the present invention is: a method for preparing a binder for a lithium ion battery, the method comprising the following steps: (1) mixing the substances contained in the first coating layer to obtain a first coating layer emulsion; (2) mixing the first coating layer latex with inorganic nanoparticles and coating them to obtain a binder precursor; (3) The substances contained in the second coating layer are mixed to obtain a second coating layer emulsion, and then the second coating layer emulsion is mixed with a binder precursor for coating to obtain a binder.
[0019] Finally, the present invention also provides the use of the binder in lithium ion batteries. The binder provided by the present invention can effectively reduce the problem of rapid capacity decay of lithium batteries caused by volume expansion of silicon particles, and is particularly suitable for use as a binder for silicon negative electrodes.
[0020] The binder described in the present invention is formed by sequentially coating inorganic nanoparticles with a first coating layer and a second coating layer of specific components. The core and the two coating layers cooperate with each other, which can not only achieve the bonding performance requirements for the silicon negative electrode, but also significantly inhibit the volume expansion of silicon, so that the silicon particles maintain a relatively fixed position, realize the elastic expansion of the silicon particles, and effectively reduce the problem of rapid attenuation of lithium battery capacity caused by the volume expansion of silicon particles. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a comparison chart of the average peel strength of the adhesives of the embodiments of the present invention and the comparative examples; Figure 2 This is a comparison chart of the first coulombic efficiency of batteries prepared with binders of the embodiment of the present invention and the comparative example; Figure 3 The figure is a comparison chart of the discharge specific capacity of the battery prepared with the binder of the embodiment of the present invention and the comparative example after 200 cycles. DETAILED DESCRIPTION
[0022] Unless otherwise specified, the raw materials used in the embodiments of the present invention are all conventional raw materials available on the market, the equipment used are all conventional equipment in the technical field, and the methods used are all conventional methods in the technical field. In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments, but it should not be regarded as a specific limitation of the present invention.
[0023] The sources of raw materials used in the following examples are as follows: Sodium tripolyphosphate powder: purchased from Liangde Nano Powder Innovation Technology (Anhui) Co., Ltd., particle size 100-200nm; Ethyl acrylate: purchased from Shandong Chuangying Chemical Co., Ltd. Polyvinyl alcohol; purchased from Guangzhou Songbai Chemical Co., Ltd.; Polyurethane: purchased from Dongguan Jincheng New Material Technology Co., Ltd.; Octylphenol polyoxyethylene ether (OP-10): purchased from Hai'an Petrochemical Plant, Jiangsu Province; Oleic acid polyoxyethylene ether: purchased from Hai'an Petrochemical Plant, Jiangsu Province; For the synthesis method of the four-arm polyacrylic acid copolymer used in the following examples, see LUO C, WU XF, ZHANGT, et al. A Four-Armed Polyacrylic Acid Homopolymer Binder with Enhanced Performance for SiOx / Graphite Anode[J]. Macromolecular Materials and Engineering, 2021, 306(1): 2000525.
[0024] The citric acid-modified carboxymethyl cellulose used in the following examples can be purchased from the market or prepared by conventional methods. The preparation methods include, but are not limited to: (1) Weigh 0.05 g of citric acid powder, add it to 2 ml of ethanol, and stir in a 50°C water bath for 30 min to fully dissolve it to obtain a citric acid alcohol solution; (2) Measure 2 ml of ultrapure water and weigh 0.05 g of carboxymethyl cellulose, add them together to the citric acid alcohol solution in step (1), and stir in a 50° C. water bath for 1 day to finally obtain citric acid-modified carboxymethyl cellulose.
[0025] Embodiment 1: An embodiment of the binder for lithium-ion batteries of the present invention, the binder of this embodiment comprises a core, a first coating layer and a second coating layer sequentially coated on the outer surface of the core; the core, the first coating layer and the second coating layer contain the following components in parts by weight: Core: 100 parts of sodium tripolyphosphate powder; First coating layer: 50 parts of ethyl acrylate, 20 parts of polyvinyl alcohol, 10 parts of polyurethane, 10 parts of octylphenol polyoxyethylene ether (OP-10), and 10 parts of oleic acid polyoxyethylene ether; Second coating layer: 10 parts of four-arm polyacrylic acid copolymer, 40 parts of citric acid-modified carboxymethyl cellulose, 25 parts of octylphenol polyoxyethylene ether (OP-10), and 25 parts of oleic acid polyoxyethylene ether.
[0026] The binder described in this embodiment is prepared by the following method: (1) mixing the substances contained in the first coating layer to obtain a first coating layer emulsion; (2) mixing the first coating layer emulsion with sodium tripolyphosphate powder and coating the mixture to obtain a binder precursor; (3) The substances contained in the second coating layer are mixed to obtain a second coating layer emulsion, and then the second coating layer emulsion is mixed with a binder precursor for coating to obtain the binder of this embodiment.
[0027] Embodiment 2: An embodiment of the binder for lithium-ion batteries of the present invention, the binder of this embodiment comprises a core, a first coating layer and a second coating layer sequentially coated on the outer surface of the core; the core, the first coating layer and the second coating layer contain the following components in parts by weight: Core: 100 parts of sodium tripolyphosphate powder; First coating layer: 80 parts of ethyl acrylate, 48 parts of polyvinyl alcohol, 16 parts of polyurethane, 28 parts of octylphenol polyoxyethylene ether (OP-10), and 28 parts of oleic acid polyoxyethylene ether; Second coating layer: 18 parts of four-arm polyacrylic acid copolymer, 42 parts of citric acid-modified carboxymethyl cellulose, 20 parts of octylphenol polyoxyethylene ether (OP-10), and 20 parts of oleic acid polyoxyethylene ether.
[0028] The preparation method of the binder described in this embodiment is the same as that in Example 1.
[0029] Embodiment 3: An embodiment of the binder for lithium-ion batteries of the present invention, the binder of this embodiment comprises a core, a first coating layer and a second coating layer sequentially coated on the outer surface of the core; the core, the first coating layer and the second coating layer contain the following components in parts by weight: Core: 100 parts of sodium tripolyphosphate powder; First coating layer: 120 parts of ethyl acrylate, 48 parts of polyvinyl alcohol, 24 parts of polyurethane, 29 parts of octylphenol polyoxyethylene ether (OP-10), and 29 parts of oleic acid polyoxyethylene ether; Second coating layer: 20 parts of four-arm polyacrylic acid copolymer, 120 parts of citric acid-modified carboxymethyl cellulose, 55 parts of octylphenol polyoxyethylene ether (OP-10), and 55 parts of oleic acid polyoxyethylene ether.
[0030] The preparation method of the binder described in this embodiment is the same as that in Example 1.
[0031] Embodiment 4: An embodiment of the binder for lithium-ion batteries of the present invention, the binder of this embodiment comprises a core, a first coating layer and a second coating layer sequentially coated on the outer surface of the core; the core, the first coating layer and the second coating layer contain the following components in parts by weight: Core: 100 parts of sodium tripolyphosphate powder; First coating layer: 22.5 parts of ethyl acrylate, 13.5 parts of polyvinyl alcohol, 4.5 parts of polyurethane, 5 parts of octylphenol polyoxyethylene ether (OP-10), 4.5 parts of oleic acid polyoxyethylene ether; Second coating layer: 15 parts of four-arm polyacrylic acid copolymer, 25 parts of citric acid modified carboxymethyl cellulose, 5 parts of octylphenol polyoxyethylene ether (OP-10), and 5 parts of oleic acid polyoxyethylene ether.
[0032] The preparation method of the binder described in this embodiment is the same as that in Example 1.
[0033] Embodiment 5: An embodiment of the binder for lithium-ion batteries of the present invention, the binder of this embodiment comprises a core, a first coating layer and a second coating layer sequentially coated on the outer surface of the core; the core, the first coating layer and the second coating layer contain the following components in parts by weight: Core: 200 parts of sodium tripolyphosphate powder; First coating layer: 105 parts of ethyl acrylate, 42 parts of polyvinyl alcohol, 21 parts of polyurethane, 41 parts of octylphenol polyoxyethylene ether (OP-10), 41 parts of oleic acid polyoxyethylene ether; Second coating layer: 50 parts of four-arm polyacrylic acid copolymer, 125 parts of citric acid modified carboxymethyl cellulose, 50 parts of octylphenol polyoxyethylene ether (OP-10), and 25 parts of oleic acid polyoxyethylene ether.
[0034] The preparation method of the binder described in this embodiment is the same as that in Example 1.
[0035] Embodiment 6: An embodiment of the binder for lithium-ion batteries of the present invention, the binder of this embodiment comprises a core, a first coating layer and a second coating layer sequentially coated on the outer surface of the core; the core, the first coating layer and the second coating layer contain the following components in parts by weight: Core: 300 parts of sodium tripolyphosphate powder; First coating layer: 47 parts of ethyl acrylate, 28 parts of polyvinyl alcohol, 10 parts of polyurethane, 10 parts of octylphenol polyoxyethylene ether (OP-10), 5 parts of oleic acid polyoxyethylene ether; Second coating layer: 7 parts of four-arm polyacrylic acid copolymer, 56 parts of citric acid modified carboxymethyl cellulose, 30 parts of octylphenol polyoxyethylene ether (OP-10), and 7 parts of oleic acid polyoxyethylene ether.
[0036] The preparation method of the binder described in this embodiment is the same as that in Example 1.
[0037] Embodiment 7: An embodiment of the binder for lithium-ion batteries of the present invention, the binder of this embodiment comprises a core, a first coating layer and a second coating layer sequentially coated on the outer surface of the core; the core, the first coating layer and the second coating layer contain the following components in parts by weight: Core: 300 parts of sodium tripolyphosphate powder; First coating layer: 125 parts of ethyl acrylate, 50 parts of polyvinyl alcohol, 25 parts of polyurethane, 50 parts of octylphenol polyoxyethylene ether (OP-10), and 50 parts of oleic acid polyoxyethylene ether; Second coating layer: 30 parts of four-arm polyacrylic acid copolymer, 80 parts of citric acid-modified carboxymethyl cellulose, 45 parts of octylphenol polyoxyethylene ether (OP-10), and 45 parts of oleic acid polyoxyethylene ether.
[0038] The preparation method of the binder described in this embodiment is the same as that in Example 1.
[0039] Embodiment 8: An embodiment of the binder for lithium-ion batteries of the present invention, the binder of this embodiment comprises a core, a first coating layer and a second coating layer sequentially coated on the outer surface of the core; the core, the first coating layer and the second coating layer contain the following components in parts by weight: Core: 83 parts of sodium tripolyphosphate powder; First coating layer: 120 parts of ethyl acrylate, 48 parts of polyvinyl alcohol, 24 parts of polyurethane, 29 parts of octylphenol polyoxyethylene ether (OP-10), and 29 parts of oleic acid polyoxyethylene ether; Second coating layer: 20 parts of four-arm polyacrylic acid copolymer, 120 parts of citric acid-modified carboxymethyl cellulose, 55 parts of octylphenol polyoxyethylene ether (OP-10), and 55 parts of oleic acid polyoxyethylene ether.
[0040] The preparation method of the binder described in this embodiment is the same as that in Example 1.
[0041] Embodiment 9: An embodiment of the binder for lithium-ion batteries of the present invention, the binder of this embodiment comprises a core, a first coating layer and a second coating layer sequentially coated on the outer surface of the core; the core, the first coating layer and the second coating layer contain the following components in parts by weight: Core: 1000 parts of sodium tripolyphosphate powder; First coating layer: 120 parts of ethyl acrylate, 48 parts of polyvinyl alcohol, 24 parts of polyurethane, 29 parts of octylphenol polyoxyethylene ether (OP-10), and 29 parts of oleic acid polyoxyethylene ether; Second coating layer: 20 parts of four-arm polyacrylic acid copolymer, 120 parts of citric acid-modified carboxymethyl cellulose, 55 parts of octylphenol polyoxyethylene ether (OP-10), and 55 parts of oleic acid polyoxyethylene ether.
[0042] The preparation method of the binder described in this embodiment is the same as that in Example 1.
[0043] Comparative Example 1: A comparative example of the binder for lithium ion batteries of the present invention, wherein the binder comprises a core and a first coating layer coated on the outer surface of the core; the core and the first coating layer comprise the following components in parts by weight: Core: 100 parts of sodium tripolyphosphate powder; First coating layer: 50 parts of ethyl acrylate, 20 parts of polyvinyl alcohol, 10 parts of polyurethane, 10 parts of octylphenol polyoxyethylene ether (OP-10), and 10 parts of oleic acid polyoxyethylene ether.
[0044] The binder described in this embodiment is prepared by the following method: (1) mixing the substances contained in the first coating layer to obtain a first coating layer emulsion; (2) The first coating layer emulsion is mixed with sodium tripolyphosphate powder and coated to obtain the binder of this comparative example.
[0045] Comparative Example 2: A comparative example of the binder for lithium ion batteries of the present invention, wherein the binder comprises a core and a first coating layer coated on the outer surface of the core; the core and the first coating layer comprise the following components in parts by weight: Core: 100 parts of sodium tripolyphosphate powder; The first coating layer: 10 parts of four-arm polyacrylic acid copolymer, 40 parts of citric acid-modified carboxymethyl cellulose, 25 parts of octylphenol polyoxyethylene ether (OP-10), and 25 parts of oleic acid polyoxyethylene ether.
[0046] The binder described in this embodiment is prepared by the following method: (1) mixing the substances contained in the first coating layer to obtain a first coating layer emulsion; (2) The first coating layer emulsion is mixed with sodium tripolyphosphate powder and coated to obtain the binder of this comparative example.
[0047] Comparative Example 3: A comparative example of the binder for lithium-ion batteries of the present invention, wherein the binder comprises a core, a first coating layer and a second coating layer sequentially coated on the outer surface of the core; the core, the first coating layer and the second coating layer comprise the following components in parts by weight: Core: 100 parts of sodium tripolyphosphate powder; First coating layer: 10 parts of four-arm polyacrylic acid copolymer, 40 parts of citric acid modified carboxymethyl cellulose, 25 parts of octylphenol polyoxyethylene ether (OP-10), and 25 parts of oleic acid polyoxyethylene ether; Second coating layer: 50 parts of ethyl acrylate, 20 parts of polyvinyl alcohol, 10 parts of polyurethane, 10 parts of octylphenol polyoxyethylene ether (OP-10), and 10 parts of oleic acid polyoxyethylene ether.
[0048] The preparation method of this comparative example is the same as that of Example 1.
[0049] Comparative Example 4: A comparative example of the binder for lithium ion batteries of the present invention, wherein the binder comprises a core, a first coating layer and a second coating layer sequentially coated on the outer surface of the core; the core, the first coating layer and the second coating layer comprise the following components in parts by weight: Core: 100 parts of sodium tripolyphosphate powder; First coating layer: 50 parts of ethyl acrylate, 20 parts of polyvinyl alcohol, 10 parts of polyurethane, 10 parts of octylphenol polyoxyethylene ether (OP-10), and 10 parts of oleic acid polyoxyethylene ether; Second coating layer: 50 parts of citric acid-modified carboxymethyl cellulose, 25 parts of octylphenol polyoxyethylene ether (OP-10), and 25 parts of oleic acid polyoxyethylene ether.
[0050] The preparation method of this comparative example is the same as that of Example 1.
[0051] Comparative Example 5: A comparative example of the binder for lithium ion batteries of the present invention, the binder in this comparative example comprises a core, a first coating layer and a second coating layer sequentially coated on the outer surface of the core; the core, the first coating layer and the second coating layer contain the following components in parts by weight: Core: 100 parts of sodium tripolyphosphate powder; First coating layer: 50 parts of ethyl acrylate, 20 parts of polyvinyl alcohol, 10 parts of polyurethane, 10 parts of octylphenol polyoxyethylene ether (OP-10), and 10 parts of oleic acid polyoxyethylene ether; Second coating layer: 50 parts of four-arm polyacrylic acid copolymer, 25 parts of octylphenol polyoxyethylene ether (OP-10), and 25 parts of oleic acid polyoxyethylene ether.
[0052] Effect Example 1: Adhesive performance test of the adhesive for lithium battery of the present invention Silicon negative electrode sheets were prepared by using the binders prepared in Examples 1 to 9 and Comparative Examples 1 to 5, respectively. The preparation methods of each group of silicon negative electrode sheets are as follows: Silicon nanoparticles, binder and conductive carbon black were fully mixed in a high-speed oscillating ball mill at a mass ratio of 7:2:1, and then evenly coated on a copper foil. The mixture was then dried at 60°C for 6 hours and then dried at 120°C in a vacuum environment for 12 hours to obtain a silicon negative electrode sheet.
[0053] A 24 mm 3M tape was pasted on the surface of the silicon negative electrode sheets prepared in each group (5 sheets in each group), and a 200 g weight was used to push the tape at a uniform speed to ensure that the tape was evenly stressed. One end of the tape and the silicon negative electrode sheet were fixed with the clamp of a universal tensile machine, and the tape was pulled at a speed of 10 mm / min to observe the peeling of the silicon negative electrode sheet, and the peeling strength of each group of silicon negative electrode sheets was recorded. The average value of each group was taken, and the results are shown in Table 1 and Appendix. Figure 1 shown.
[0054]
[0055] As can be seen from the results of Table 1, Examples 1 to 9 all have strong peel strengths, and the adhesives of the embodiments 1-9 of the specification have good bonding properties. Compared with Example 1, Comparative Example 1 differs only in that it does not contain the first coating layer in Example 1, and Comparative Example 1 also has a higher peel strength, indicating that the bonding properties of the adhesive of the present invention are mainly brought by the second coating layer. Compared with Example 1, Comparative Examples 2 and 3 differ mainly in that the outermost layer of the adhesive is the first coating layer rather than the second coating layer. As can be seen from the significant decrease in the peel strength of Comparative Examples 2 and 3 compared with Example 1, the bonding properties of the first coating layer in the adhesive of the present invention are much lower than the second coating layer. Compared with Example 1, Comparative Examples 4 and 5 mainly differ in that the second coating layer contains only one of the four-arm polyacrylic acid copolymer and the citric acid-modified carboxymethyl cellulose. As can be seen from the comparison of the peel strength of Comparative Examples 4 and 5 with Example 1, the four-arm polyacrylic acid copolymer and the citric acid-modified carboxymethyl cellulose cooperate to promote each other and synergize the bonding properties of the adhesive.
[0056] Effect Example 2: Electrochemical performance of lithium battery prepared using the binder of the present invention The performance of the battery was tested by assembling button-type half-cell CR2032. The silicon negative electrode sheets prepared in Examples 1 to 9 and Comparative Examples 1 to 5 in Effect Example 1 were used as working electrodes, metal lithium sheets (15 mm × 0.6 mm) were used as counter electrodes, battery shells (CR2032), stainless steel gaskets (1 mm thick), and spring sheets (1 mm thick) were used.
[0057] The assembly method of CR2032 battery is as follows: the electrode sheet after vacuum drying at 120℃ is cut into pieces with a diameter of 1.54 cm 2 The circular pole piece is used for battery assembly. The button cell is assembled in a glove box filled with argon. The glove box environment is strictly controlled to keep the water pressure and oxygen pressure below 1 ppm to prevent lithium metal oxidation. The positive electrode shell / silicon negative electrode / diaphragm / metal lithium sheet / stainless steel gasket / spring sheet / negative electrode shell are assembled in order, and 0.1 mL of electrolyte is added. The electrolyte (1 mol / L lithium hexafluorophosphate (LiPF6) is dissolved in a 1:1 volume ratio of ethylene carbonate (EC) and diethyl carbonate (DEC) solvent, and 10% mass fraction of fluoroethylene carbonate (FEC) is added. Then, the CR2032 battery is pressure-sealed using a button cell sealer with a sealing pressure of 1000 psi to obtain a CR2032 half-cell, which is left to stand for 12 hours for electrochemical performance testing.
[0058] The Blue Electric Battery Testing System tests the electrochemical performance of button half-cells at a temperature of 25°C and a voltage range of 0.01-1.2V. The test method is to activate for 3 cycles at a current density of 0.1C and cycle for 200 cycles at a current density of 0.2C. The scan rate of the cyclic voltammetry (CV) test is 0.2mV / s and the potential range is 0.01-3.0V.
[0059] The first coulombic efficiency of each group of batteries tested and the discharge specific capacity after 200 cycles at a current density of 0.2C are shown in Table 2 and Appendix. Figure 2 and 3 shown.
[0060]
[0061] It can be seen from the results in Table 2 that the battery assembled from the silicon negative electrode sheet prepared by the binder of the present invention has more excellent electrochemical performance.
[0062] It can be seen from the comparison of Comparative Examples 1-3 with Example 1 that the core, the first coating layer and the second coating layer in the binder of the present invention are composed in a certain order, and the three together achieve the effect of improving the electrochemical performance of the silicon negative electrode sheet.
[0063] It can be seen from the comparison of Comparative Examples 4 and 5 with Example 1 that in the binder of the present invention, the combination of the four-arm polyacrylic acid copolymer and the citric acid-modified carboxymethyl cellulose in the second coating layer can better keep the silicon particles in a relatively fixed position, thereby effectively solving the problem of rapid capacity decay of lithium batteries caused by the volume expansion of silicon particles.
[0064] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A binder for lithium ion batteries, characterized in that: The binder comprises a core, a A first coating layer and a second coating layer covering the outer surface of the core; The core is an inorganic nanoparticle; the first coating layer includes ethyl acrylate, polyvinyl alcohol, polyurethane and a first emulsifier; The second coating layer includes four-arm polyacrylic acid copolymer, modified carboxymethyl cellulose and a second emulsifier, and the mass ratio of the four-arm polyacrylic acid copolymer to the modified carboxymethyl cellulose is (1-3): (5-8).
2. The binder for lithium ion batteries according to claim 1, characterized in that: The modified carboxymethyl cellulose in the second coating layer is citric acid modified carboxymethyl cellulose.
3. The binder for lithium ion batteries according to claim 1 or 2, characterized in that: In the second coating layer, the sum of the mass percentages of the four-arm polyacrylic acid copolymer and the modified carboxymethyl cellulose is 50-80%.
4. The binder for lithium ion batteries according to claim 1, characterized in that: The inorganic nanoparticles are at least one of sodium tripolyphosphate powder, silicon dioxide nanoparticles, and titanium dioxide nanoparticles; the particle size of the sodium tripolyphosphate powder is 1 to 1000 nm; And / or, the first emulsifier and the second emulsifier are each independently selected from at least one of octylphenol polyoxyethylene ether, polyoxyethylene-8-octylphenyl ether, and oleic acid polyoxyethylene ether.
5. The binder for lithium ion batteries according to claim 1, characterized in that: The sum of the mass percentages of ethyl acrylate, polyvinyl alcohol and polyurethane in the first coating layer is 65-85%.
6. The binder for lithium ion batteries according to claim 5, characterized in that: The mass ratio of ethyl acrylate, polyvinyl alcohol and polyurethane in the first coating layer is 5:(2-3):
1.
7. The binder for lithium ion batteries according to claim 1, characterized in that: The mass ratio of the core to the first coating layer and the second coating layer is: core: (first coating layer + second coating layer) = (1-3): (2-5).
8. The binder for lithium ion batteries according to claim 1 or 7, characterized in that: The mass ratio of the first coating layer to the second coating layer is (1~2):
1.
9. A method for preparing a binder for lithium ion batteries according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: (1) mixing the substances contained in the first coating layer to obtain a first coating layer emulsion; (2) mixing the first coating layer latex with inorganic nanoparticles and coating them to obtain a binder precursor; (3) The substances contained in the second coating layer are mixed to obtain a second coating layer emulsion, and then the second coating layer emulsion is mixed with a binder precursor for coating to obtain a binder.
10. Use of the binder according to any one of claims 1 to 8 in a lithium ion battery.
Citation Information
Patent Citations
Lithium ion battery binding agent and preparation method and application thereof
CN109786747A
Large-particle emulsion type binder and preparation method thereof, battery diaphragm and lithium ion battery
CN119119925A
Binder for negative electrode of secondary battery, negative electrode of secondary battery and secondary battery
JP2015210931A
Superoxide dismutase and uses thereof for preventing or treating dry macular degeneration
KR102531246B1
Aqueous binder for lithium ion battery, preparation method therefor and use thereof
US20180248191A1